(untitled) (ENTHYMEMA, 2010)
The essay analyzes the work of Paul de Man (1919-1983), in particular Allegories of Reading. Even though his posthumously revealed ties with Nazism reduced his academic influence, de Man is still considered the leader of Deconstruction in America, and his favorite metaphor of ’seduction’ summarizes his Nietzschean theory of rhetoric as illusionism, i.e. a strategy that provoke an affective reaction, independent from logic or facts. Yet, this metaphor seems to be in contrast with other tendencies of Deconstruction, namely the self-referential, non-voluntary, autonomous status of writing, the absence of critical meta-language, the reduction of psychology in criticism.